An epidemiologic comparison of high school and college wrestling injuries - Yard, E. E.; Collins, C. L.; Dick, R. W.; Comstock, R. D. (The American Journal of Sports Medicine, 2008)
Wrestling holds worldwide popularity, and large numbers of United States high school and college males participate. However, the sport`s arduous nature results in high injury rates.